Effect of Micronutrient Metal Ions on the Inhibition Efficiency of Citric Acid Towards the Mineralisation of Urinary Stone Forming Minerals - Rao, T.V.R.K.; Choudhry, V.K. (Asian Journal of Chemistry, 2010)
Effect of micronutrient metal ions, viz., Cr3+, Mn2+, Fe2+, Co2+, Ni2+, Cu2+ or Zn2+ on the inhibition efficiency of citric acid towards the mineralisation of urinary stone forming minerals, viz., calcium phosphate, calcium oxalate or calcium carbonate has been studied in an experimetaI model. Utility of the results in urolithiasis inhibition has been discussed.